2016
DOI: 10.1016/j.jpainsymman.2016.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Terminal Hospitalization Care Between U.S. Men and Women

Abstract: Men who die in hospitals receive more aggressive care than women. Further research should examine potential causes of this overall pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…Living Situation: Studies appraised showed women were less likely married, more likely to be widowed and more likely to be living alone at the end of life. 30,31,34 This is in keeping with demographic trends, in that women outlive men and tend to be older at the end of life. 31,32 However, this longevity did not translate into well-being, as many chronic diseases and chronic pain conditions were more prevalent among women.…”
Section: Thematic Analysissupporting
confidence: 63%
See 3 more Smart Citations
“…Living Situation: Studies appraised showed women were less likely married, more likely to be widowed and more likely to be living alone at the end of life. 30,31,34 This is in keeping with demographic trends, in that women outlive men and tend to be older at the end of life. 31,32 However, this longevity did not translate into well-being, as many chronic diseases and chronic pain conditions were more prevalent among women.…”
Section: Thematic Analysissupporting
confidence: 63%
“…30,31,34 This is in keeping with demographic trends, in that women outlive men and tend to be older at the end of life. 31,32 However, this longevity did not translate into well-being, as many chronic diseases and chronic pain conditions were more prevalent among women. 5 Oftentimes women were left alone at the end of life after having expended much time, energy, and resources to care for spouses and help them have a good death, leaving these women without a spouse and with fewer resources as they approached death.…”
Section: Thematic Analysissupporting
confidence: 63%
See 2 more Smart Citations
“…Prior studies have shown that many patient (sex, ethnicity, comorbidities, insurance status) and health system (bed size, urban/rural location, tax status) characteristics affect how stroke patients are treated at the end of life. 4 We should accept some degree of variation in the process of shared decision-making to explain these differences. This variation may include differences in patient and surrogate preferences as well as differences in patient-centered communication skills, including clinicians' ability to prognosticate and elicit values and preferences.…”
mentioning
confidence: 99%